Reducing orthopaedic hazards of the computer work environment. - Doheny M; Linden P; Sedlak C (Orthopaedic Nursing)
The rate of repetitive strain injuries (RSI) in the workplace is rising at an alarming rate. People using computers and working at keyboards for long periods of time are particularly at risk. Prevention of orthopaedic injuries can make the work environment less stressful and more productive as well as help to avoid needless human suffering and costly medical and legal bills. Knowledge of the causes of RSI and preventive measures to reduce orthopaedic hazards of the computer work environment is important for orthopaedic nurses.